Penny Postcard Image of Lemon Packing House in Santa Paula, CA - United States Post Office::::::
Penny postcard of one of the early lemon packing houses for the Limoniera Company. The Limoneira Company was founded by N. W. Blanchard, W.L. Hardison, C.M. McKevett, A.J. Hardison and C.C. Teague in 1893. Image digitized by Broome Library, California State University Channel Islands. Original 35mm slide housed at E.P. Foster Library, Ventura, California.